The effect woven fabric styles and honeycomb core properties composite parts: a review - Mohd Razali, Muhamad; Mohammad Hamdan, Mohd Sanusi (2011)
Advanced composite laminate and honeycomb sandwich structure depict process induced geometrical and dimensional deformations after end of curing process and when removed from its mould tools. A simple flat part tends to warp while an angled or curved part indicates spring-in phenomenon due to the anisotropic material properties. These shape deformations are unpredictable and contribute to fit, fonn and functional error during an assembly stage. Often a conventional trialand-error method is deployed to correct the mould tool shape prior to mass production, which is very costly, uneconomical and time consuming. Alternatively a better method is sought to intelligently predict shape deformations considering the material properties, tool-part interaction and processing factors through analytical model, experiments and numerical analysis. However, experimental data is lacking in understanding the effect of fiber weaving styles and honeycomb core material properties in inducing shape deformations. Using higher satin weave style in the composite fabrication is believed to reduce the shape deformations. While adding a honeycomb core between solid laminate skins reduces shape deformation due to its high stiffness to weight ratio. The degree and magnitude of both factors in influencing shape deformations are unknown. Hence, it is proposed to perform design of experiment using Design Expert software with eight key process parameters such as lay-up orientation, number of layers, part geometry, part size, fiber volume, part configuration, weaving style and tool material to provide more insights of process induced shape deformations of monolithic and honeycomb sandwich composite structure.